Measuring motivation in a cichlid fish: An adaptation of the push-door paradigm - Galhardo, Leonor (2012)
Recent behavioural, cognitive and neurophysiological studies strongly suggest that fish are capable of psychological experiences. Therefore, identifying needs from the animals’ point of view is likely to be one of the best approaches to understand their welfare. Motivational tests, as a measure of what animals want, have been developed and refined for some decades. Despite numerous studies on fish motivational systems, none have attempted to quantify their motivation using this approach. Motivation studies often imply operant tasks for which various devices are used. The aim of this study was to adapt a push-door to quantify motivation in a cichlid fish, the Mozambique tilapia (Oreochromis mossambicus). Males of this species have strong snouts which they use for a number of activities and are thus suited to push. Twelve males of different social status were tested for three kinds of reinforcers: food, social partner and a control (additional space with substrate only). The animals were required to work the door (push/touch) at an ascending cost in order to have access to the resources. Measures of motivation included latency to open the door, work attention and maximum price paid. Latency to open the door increased with increasing cost for all resources, with the highest latency for the control reinforcer. Work attention was constant with increasing costs for social partners and food, and higher than the control. Work attention decreased for the control as cost increased. Maximum price paid was consistent with these results, being higher for social partners and food than for the control. The results of the three measures were consistent with each other and showed that the push-door can be used to measure motivation in this species. Further refinement of the present experimental set up will allow the use of this paradigm in the future, in order to improve knowledge on how this species values and ranks its needs.